Comparison between the effects of the losartan and enalapril on uric acid concentration in hypertensive patients (Tikrit Journal of Pharmaceutical Sciences, 2023)
A total of 80 patients with mild to moderate hypertension were divided into two groups, the 1st group treated by losartan 50mg/day, 2nd group on enalapril 20mg/day, for 4 weeks duration, along with 41 apparently healthy persons (control group) were included in this study. The aim of this study comparison between losartan and enalapril effects on serum uric acid level. For each patient (before and after therapy)and control, blood pressure and serum uric acid level were measured. Results of this study were shown both losartan and enalapril are effective in reducing blood pressure when compared before and after treatment, (however, enalapril is more effective), only losartan is significantly reducing serum uric level